ZTE MR-based attenuation correction in brain FDG-PET/MR: performance in patients with cognitive impairment. - Sgard, Brian; Khalifé, Maya; Bouchut, Arthur; Fernandez, Brice; Soret, Marine; Giron, Alain; Zaslavsky, Clara; Delso, Gaspar; Habert, Marie-Odile; Kas, Aurélie (European Radiology, 2020)
Objective: One of the main challenges of integrated PET/MR is to achieve an accurate PET attenuation correction (AC), especially in brain acquisition. Here, we evaluated an AC method based on zero echo time (ZTE) MRI, comparing it with the single-atlas AC method and CT-based AC, set as reference.Methods: Fifty patients (70 ± 11 years old, 28 men) underwent FDG-PET/MR examination (SIGNA PET/MR 3.0 T, GE Healthcare) as part of the investigation of suspected dementia. They all had brain computed tomography (CT), 2-point LAVA-flex MRI (for atlas-based AC), and ZTE-MRI. Two AC methods were compared with CT-based AC (CTAC): one based on a single atlas, one based on ZTE segmentation. Impact on brain metabolism was evaluated using voxel and volumes of interest-based analyses. The impact of AC was also evaluated through comparisons between two subgroups of patients extracted from the whole population: 15 patients with mild cognitive impairment and normal metabolic pattern, and 22 others with metabolic pattern suggestive of Alzheimer disease, using SPM12 software.Results: ZTE-AC yielded a lower bias (3.6 ± 3.2%) than the atlas method (4.5 ± 6.1%) and lowest interindividual (4.6% versus 6.8%) and inter-regional (1.4% versus 2.6%) variabilities. Atlas-AC resulted in metabolism overestimation in cortical regions near the vertex and cerebellum underestimation. ZTE-AC yielded a moderate metabolic underestimation mainly in the occipital cortex and cerebellum. Voxel-wise comparison between the two subgroups of patients showed that significant difference clusters had a slightly smaller size but similar locations with PET images corrected with ZTE-AC compared with those corrected with CT, whereas atlas-AC images showed a notable reduction of significant voxels.Conclusion: ZTE-AC performed better than atlas-AC in detecting pathologic areas in suspected neurodegenerative dementia.Key Points: • The ZTE-based AC improved the accuracy of the metabolism quantification in PET compared with the atlas-AC method. • The overall uptake bias was 21% lower when using ZTE-based AC compared with the atlas-AC method. • ZTE-AC performed better than atlas-AC in detecting pathologic areas in suspected neurodegenerative dementia.